Physical and chemical effects of acoustic cavitation in selected ultrasonic cleaning applications - Yusof, N.S.M.; Babgi, B.; Alghamdi, Y.; Aksu, M.; Madhavan, J.; Ashokkumar, M. (Elsevier, 2016)
Acoustic cavitation in a liquid medium generates several physical and chemical effects. The oscillation and collapse of cavitation bubbles, driven at low ultrasonic frequencies (e.g., 20 kHz), can generate strong shear forces, microjets, microstreaming and shockwaves. Such strong physical forces have been used in cleaning and flux improvement of ultrafiltration processes. These physical effects have also been shown to deactivate pathogens. The efficiency of deactivation of pathogens is not only dependent on ultrasonic experimental parameters, but also on the properties of the pathogens themselves. Bacteria with thick shell wall are found to be resistant to ultrasonic deactivation process. Some evidence does suggest that the chemical effects (radicals) of acoustic cavitation are also effective in deactivating pathogens. Another aspect of cleaning, namely, purification of water contaminated with organic and inorganic pollutants, has also been discussed in detail. Strong oxidising agents produced within acoustic cavitation bubbles could be used to degrade organic pollutants and convert toxic inorganic pollutants to less harmful substances. The effect of ultrasonic frequency and surface activity of solutes on the sonochemical degradation efficiency has also been discussed in this overview.